Efficacy of Valsalva Maneuver on Pain and Vasovagal Response during Removal Femoral Sheath Post Percutaneous Coronary Intervention - Noor Al-Huda Al-ziyadi,; Mohammed Hakim Shamran Al-Hchaim,; Ahmed Nema Rjeeb, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The obstructed coronary artery can be re vascularized through a minimally invasive procedure called the percutaneous coronary Intervention (P.C.I). Many complications might occur through the femoral sheaths was removed such as pain and vasovagal response, that may induce morbidity and mortality. Study Aim: To evaluate the efficacy of Valsalva maneuver on pain and vasovagal response during removal femoral sheath post PCI. Methods:A quasi experimental design, was performed at the AL-Najaf Center for Cardiac Surgery and Cardiac Catheterization in Al-Najaf AL Ashraf city between (16th October to 1st December 2024). A non-probability (purposive sample) of (128) patients after elective PCI. Result: The current result indicated that there is a significant reduction in pain and vasovagal response during the removal of the femoral sheath. Conclusion:The Valsalva maneuver was effective in relieving complications during removal femoral sheath. Recommends: Accepting into consideration the finding of the current should use pharmacological methods such as Valsalva maneuver to relieve pain intensityand prevent vasovagal response.